Defining the Role of Neoadjuvant Chemotherapy Followed by Surgery in Locally Advanced Cancer Cervix: A Meta-analysis of Phase III Trials - Osman, Mohammed A. (J Obstet Gynaecol India, 2015)
STUDY OBJECTIVES: This meta-analysis was performed to compare the outcomes between NACT-S and RT for locally advanced cancer cervix. The primary end points were survival benefits. SEARCHING METHOD: The data sources for the search included medline, national library of medicine, and the embase search engines. Inclusion criteria included studies published between 2000 and 2012, and FIGO stages IB2 to IVA. Studies had to be properly randomized, prospective, or retrospective and only phase III. Further, the studies had to be with two arms, including one arm for neoadjuvant chemotherapy then-surgery (NACT-S), and the other arm for radiotherapy (RT). RESULTS: Data were collected from 1171 patients enrolled in seven phase III trials. The 5-year PFS (progression-free survival) for NACT-S and RT were 62 and 45.5 %, respectively. The 5-year OS for NACT-S and RT were 66 and 49 %, respectively. NACT-S was associated with better late toxicities compared to RT. CONCLUSION: NACT-S is a reasonable treatment option for locally advanced cancer cervix. It achieved better results than RT, especially for stages from IB2 to IIB.